National Interest And National Identity - An Interrogation Of Aurobindo's Nationalism Is Religion - TS, Yashavantha; H.K, Shivalingaswamy (International Journal of Psychosocial Rehabilitation, 2024)
This paper undertakes an in-depth exploration of Sri Aurobindo's paradigm of nationalism as a form of religion, as it pertains to the nexus of national interest and identity. Aurobindo's philosophical underpinnings espouse a unique combination of spiritualism and nationalism, asserting that national interest and identity are as much spiritual as they are political. The research primarily aims to deconstruct this philosophy, scrutinizing its implications for the conception of nationalism in contemporary discourse. Furthermore, the paper dissects Aurobindo's assertion that every nation has a "Dharma," or a spiritual mission that is integral to its national identity. Analyzing the intersection of national interest and identity in the light of Aurobindo's philosophy, the paper evaluates the potential challenges and benefits posed by this perspective in a multicultural and globalized world. The investigation follows an interdisciplinary approach, bridging the fields of philosophy, political science, and sociology to offer a comprehensive understanding of Aurobindo's 'Nationalism is Religion'. The study concludes by offering new insights into the discourse on nationalism, emphasizing the importance of spiritual underpinnings in shaping national identity and interest.